COMPARISON OF DIFFERENT METHODS OF PHYSIOTHERAPY TREATMENT IN THE MANAGEMENT OF PRIMARY OPEN-ANGLE GLAUCOMA - T. G. Kamenskikh; E. V. Veselova; I. D. Kamenskikh (Alʹmanah Kliničeskoj Mediciny, 2016)
Background: Therapeutic action of physical therapy aims at the recovery of conductibility of optic tracts, improvement of microcirculation and hemodynamics, stimulation of regulatory brain structures and improvement of psycho-neurological status of patients. Aim: To assess efficacy of transcranial magnetic therapy, contemporary transcranial magnetic therapy/electrostimulation and magnetic sympathocorrection in the treatment of primary open-angle glaucoma. Materials and methods: 397 patients (634 eyes), aged 58–76 years, with verified diagnosis of stage I, II or III primary open-angle glaucoma, received transcranial magnetic therapy (group 1, 182 eyes), contemporary transcranial magnetic  herapy/electrostimulation (group 2, 258 eyes) and magnetic sympathocorrection (group 3, 194 eyes). All patients underwent routine ophthalmological examination, visual evoked potential recording and assessment of ocular circulation. Results: In patients with initial stage of glaucoma, most prominent changes of electrophysiological parameters was demonstrated in the group 2: visual evoked potential amplitude increased from 8.4 ± 0.4 to 11.3 ± 0.2 mcV, latency decreased from 77.6 ± 1.3 to 70.4 ± 2.1 ms. Maximal improvement of ocular circulation (decrease of resistance index of posterior short ciliary arteries from 0.69 ± 0.02 to 0.51 ± 0.03) was registered in the group 3. In patients with evolved glaucoma (stage II), significant increase of P100 amplitude of visual evoked potentials (from 7.5 ± 0.2 to 9.8 ± 0.3 mcV) was found in the group 2; latency period decreased from 84.6 ± 1.5 to 74.8 ± 2.1 ms. In stage II glaucoma patients, prominent increase of systolic blood velocity was demonstrated in groups 3 and 2: from 11.26 ± 0.8 to 13.64 ± 0.63 cm/s and from 10.5 ± 0.2 to 13.9 ± 0.7 cm/s, respectively. Resistance index decreased from 0.76 ± 0.05 to 0.52 ± 0.02 and from 0.75 ± 0.02 to 0.65 ± 0.02 in groups 3 and 2, respectively. In advanced glaucoma (stage III), most prominent increase of P100 amplitude of visual evoked potentials was demonstrated in group 2: amplitude of visual evoked potentials increased from 6.5 ± 0.2 to 8.1 ± 0.2 mcV, latency decreased from 87.5 ± 2.3 to 80.1 ± 2.1 ms. Maximal improvement of ocular circulation (increase of systolic blood velocity from 9.2 ± 0.72 to 11.2 ± 0.6 cm/s) and decrease of resistance index (from 0.84 ± 0.04 to 0.66 ± 0.03) was found in patients with stage III glaucoma in the group 3. Conclusion: Use of different methods of magnetic therapy especially in combination with electrostimulation activates ocular hemodynamics and stimulates bioelectric activity of visual cortex and may prevent visual functions impairment in glaucoma.